2011
DOI: 10.1051/0004-6361/201117318
|View full text |Cite
|
Sign up to set email alerts
|

VLT observations of the twoFermipulsars PSR  J1357−6429 and PSR  J1048−5832

Abstract: Context. Optical observations of pulsars are crucial to studying the neutron star properties from the structure and composition of the interior to the properties and geometry of the magnetosphere. Historically, X and γ-ray observations have paved the way to pulsar optical identifications. The launch of the Fermi Gamma-ray Space Telescope opened new perspectives in the optical-to-γ-ray studies of neutron stars with the detection of more than 80 γ-ray pulsars. Aims. Here, we aim to search for optical emission fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
41
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 34 publications
13
41
1
Order By: Relevance
“…The 5σ offset of the source from the pulsar radio interferometric position, which was obtained ≈9 years earlier (Camilo et al 2004), implied a very high pulsar transverse velocity of ≈ 2000d 2.5 km s −1 (Danilenko et al 2012). Similar velocity was obtained by Mignani et al (2011) based on the comparison of the pulsar radio and X-ray positions. However, Kirichenko et al (2015) showed that Camilo et al (2004) underestimated the uncertainties of the pulsar radio position obtained with the Australia Telescope Compact Ar- ray (ATCA) in 2000.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The 5σ offset of the source from the pulsar radio interferometric position, which was obtained ≈9 years earlier (Camilo et al 2004), implied a very high pulsar transverse velocity of ≈ 2000d 2.5 km s −1 (Danilenko et al 2012). Similar velocity was obtained by Mignani et al (2011) based on the comparison of the pulsar radio and X-ray positions. However, Kirichenko et al (2015) showed that Camilo et al (2004) underestimated the uncertainties of the pulsar radio position obtained with the Australia Telescope Compact Ar- ray (ATCA) in 2000.…”
Section: Introductionsupporting
confidence: 82%
“…The J1357 field was observed in the optical V RI bands with the ESO Very Large Telescope (VLT) in 2009 (Mignani et al 2011;Danilenko et al 2012). Danilenko et al (2012) detected a point source in all these bands within 1σ uncertainties of the pulsar X-ray position and suggested it as a pulsar optical counterpart candidate.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting point to mention is that the elongation of the detected X-ray PWN, about 60 • to northeast, may indicate the direction of the pulsar's proper motion (see also Mignani et al 2011). …”
Section: Spatial and Spectral Analysis Of The X-ray Datamentioning
confidence: 99%
“…Recently, Very Large Telescope data were used to search for optical emission from PSR J1357−6429 (Mignani et al 2011). No counterpart was found, and an upper limit of V 27 was determined.…”
Section: Introductionmentioning
confidence: 99%
“…A possible detection of J1357 with AGILE at lower γ -ray energies (100 MeV-10 GeV) was reported by Pellizzoni et al (2009). 5 No optical counterpart to the pulsar or its PWN has been detected yet (Mignani et al 2011).…”
Section: Introductionmentioning
confidence: 99%